Intelligence snatchs robot - ZHAO QIANG; WU XIONGHUI; LIU XINJIAN; LIU YANG; ZHANG YINLEI; SI CHANG (2018)
The utility model relates to a robotechnology field, the utility model provides an intelligence snatchs robot, it includes the grasping system, the bootstrap system, frame and running gear, the grasping system includes arm and grabbing device, the arm is connected with the frame, grabbing device connects on the arm, the bootstrap system is used for the position and the shape information of the identifier body, thereby discernment and judgement to the position of the subject and shape information have been realized, and draw guide action and walk the device, the arm, grabbing device carries outcorresponding motion, thereby realize snatching the intelligence of object, the specially adapted snatchs the position in succession, the equal uncertain a plurality of objects of shape. 本实用新型涉及机器人技术领域，提供了种智能抓取机器人，其包括抓取系统、引导系统、机架和行走装置，抓取系统包括机械臂和抓取装置，机械臂与机架连接，抓取装置连接在机械臂上，引导系统用于识别物体的位置和形状信息，从而实现了对物体位置和形状信息的识别和判断，并引导行走装置、机械臂、抓取装置进行相应的运动，从而实现对物体的智能抓取，特别适用于连续抓取位置、形状均不确定的多个物体。